(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The Kazakh landed in Europe. These are golden pages of history of the country. Fifty-five countries of the three continents meet and discuss the world-class problems, and the right to common speech is a tremendous responsibility. Each member of the team, in turn, turns the presidency in fifty-five years.